Decentralization Can Improve Equity, but Can It Be Sustained? - Thomas J. Bossert; Rony Lenz; Ramiro Guerrero; Rene Miranda; Victoria Eugenia Soto Rojas; Norman Danilo Maldonado Vargas (Taylor & Francis Group, 2022)
AbstractA major theoretical issue about health system reform involving decentralization has been whether it promotes equity of health system funding. An article by the principal author and others in 2003 showed that, under certain conditions and policies, decentralization improved the equity of allocation of financial resources to different income levels of municipalities in Colombia and Chile. Another recurring issue has been whether reforms can be sustained over time. In a follow-up study in 2015, we found that the equity of national allocations was sustained even though the allocation rules for intergovernmental transfers and insurance funding sources had changed, as long as per capita allocation rules were retained. Nevertheless, the wealthier municipalities in Chile were able to increase their own source funding contributing to a larger gap between wealthy and poor municipalities, suggesting that in order to assure continued equity some compensation for these funds be included in intergovernmental transfer rules or that local source funding be restricted by national policy. These reforms may be more likely to be sustained if they become embedded in existing financial systems and if they receive support of status quo constituencies.